2019
DOI: 10.1016/j.envres.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Higher plasma oxidative damage and lower plasma antioxidant defences in an Arctic seabird exposed to longer perfluoroalkyl acids

Abstract: Perfluoroalkyl and polyfluoroalkyl substances (PFASs) may cause detrimental effects on physiological function and reproduction of Arctic animals. However, there is a paucity of information on the link between PFASs and oxidative stress, which can have potential detrimental effects on key fitness traits, such as cellular homeostasis or reproduction. We have examined the correlations between multiple blood-based markers of oxidative status and several perfluoroalkyl carboxylic acids (i.e., with 8 or more carbons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…Animal studies have also shown that PFAS disrupt normal thyroid function [56] and biosynthesis of thyroid and reproductive hormones [55,57]. Another possible mechanism may be elevated oxidative stress, which has been associated with increased odds of PTB [58] and is hypothesized to be a downstream consequence of PFAS exposure [59]. PBDEs may affect birth outcomes through disruption of thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have also shown that PFAS disrupt normal thyroid function [56] and biosynthesis of thyroid and reproductive hormones [55,57]. Another possible mechanism may be elevated oxidative stress, which has been associated with increased odds of PTB [58] and is hypothesized to be a downstream consequence of PFAS exposure [59]. PBDEs may affect birth outcomes through disruption of thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, exposure to PFAS did not produce any change in enzymatic activity, as in Japanese medaka after treatment with PFOA [322], in Arctic kittiwakes (Rissa sp.) that accumulate PFAS from the environment [325], or in chicken experimentally exposed to PFOS [319].…”
Section: Biochemical Datamentioning
confidence: 99%
“…In some cases, exposure to PFAS did not produce any change in enzymatic activity, as in Japanese medaka after treatment with PFOA [319], in Arctic kittiwakes (Rissa sp.) that accumulate PFAS from the environment [322], or in chicken experimentally exposed to PFOS [316].…”
Section: Biochemical Datamentioning
confidence: 99%